Extreme Hyperferritinemia in Dizygotic Twins With Human Parechovirus-3 Infection. Issue 12 (December 2016) - Casas-Alba, Dídac; Martínez-Monseny, Antonio; Monfort, Laura; Muñoz-Almagro, Carmen; Cabrerizo, María; Deyà, Àngela; Launes, Cristian
Abstract : Human parechovirus-3 has been associated with severe clinical manifestations in infants, such as sepsis-like illness and meningoencephalitis. Nevertheless, the vast majority of patients have a favorable outcome. We report the occurrence of this infection in dizygotic infants with extreme hyperferritinemia and a transient impairment of natural killer cell cytotoxicity.